Future Development of Customer Analytics in Marketing (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
Customer Analytics is a fairly new part of business analytics. It has brought new, granular approach to customers. Since it is developing along with technology, a lot has changed since its beginnings in the 60's and 70's. As marketing relies on customer analytics, it is important to know where the analytics are heading and how marketing can benefit from it. The goal of this paper is to show the possible future development of customer analytics in marketing. It is going to be achieved by an extensive literature review on this topic, with the focus on the latest findings in these fields.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.